Philosophische Grundbegriffe Sozialer Arbeit - Nathschläger, Johannes (Nomos Verlagsgesellschaft mbH & Co. KG, 2026)
How can philosophy enrich social work? This book offers a compact and clear introduction to the central philosophical concepts and topics that students and professionals in social work are confronted with – including social justice, freedom, responsibility, power, community, meaning and helping. With comprehensible explanations, critical reflections and practical applications, this book offers a well-founded introduction for students and professionals and shows the direct relevance for reflective thinking and professional action in social work. Because philosophy is not a luxury – it is the basis for intelligent and reflective social action.Prof. Dr. phil. Johannes Nathschläger is Professor of Theories, Methods and Concepts of Social Work at the Catholic University of Applied Sciences NRW in Münster. He is a qualified social pedagogue, logotherapist and addiction counselor and holds a doctorate in philosophy.The book will also be available in open access upon publication.